Pengaruh Model Pembelajaran Value Clarification Technique (VCT) Berbasis Kearifan Lokal Madura Terhadap Hasil Belajar Siswa Pada Tema 7 Subtema 2 Kelas V SDN Tanamerah 2 Sumenep - Putri Hania; Isna Ida Mardiyana (Jurnal Riset Madrasah Ibtidaiyah, 2023)
The purpose of this study was to determine the effect of the Value Clarification Technique (VCT) model based on Madurese local wisdom in improving student learning outcomes on the theme 7 subthemes 2 Class V Elementary School. This study is an experimental study. This type of research is a Quasi Experimental Design with Prestest-Posttest Control Group Design. This study was conducted in the 2022/2023 academic year with research respondents from Grade V students with an experimental group of 20 and a control group of 20. Instruments using learning outcomes tests and documentation. The Data obtained were analyzed using the T-test with the Formula Independent Sample T-Test. The results of this study showed that the Value Clarification Technique (VCT) model based on Madurese local wisdom has an effect on the learning outcomes obtained t count value of 6.047 and ttable on (df.38) significance of 0.05 by 1.686, and the results of GIS. 2-tailed by 0.000 < 0.05. So it is concluded that Ha is accepted and H0 is rejected because the count > ttable. In essence, the application of the VCT model can improve student learning outcomes. This research contributes to improving the quality and results of local wisdom-based learning in accordance with the independent curriculum.